Penerapan metode Analytical Hierarchy Process dan Simple Additive Weighting untuk Pemilihan Supplier pada Bengkel - Anita Diana; Dwi Achadiani (Maranatha University Press, 2022)
The selection of suppliers at the workshop aims to make it easier for workshop owners to determine suppliers in purchasing spare parts. This research case study takes place at the Prima Motor Sport Workshop, where in the process, there is no annual supplier selection process. The obstacle encountered is the absence of an appropriate method for selecting the selected supplier, making it difficult to determine the supplier in purchasing goods. Therefore, there is a need for research to determine the right method in selecting suppliers at the workshop. The methods used are Analytical Hierarchy Process (AHP) and Simple Additive Weighting (SAW). The AHP method is used because it is one of the popular methods for finding the weighting value for each set criterion, namely delivery time, quality of goods, warranty, and price. The SAW method can display alternative sequence priorities in the form of the highest to the lowest ranking, is easy to implement, and uses the concept of weighting. This research produces the right method in data processing to make it easier for workshop owners to choose more objective suppliers every year.